An Overview on Computational Techniques in Textile Engineering (Journal of Fiber Bioengineering and Informatics, 2008)
This paper discusses a number of computational problems in textile/garment industry. Theseproblems cover quality inspection of textile products, on-line process control and monitoring, processand material modeling and simulation, CAD for clothing and materials, and computerized managementof production and supply chain. Recently, more attention has been paid to modeling and analysisof human related complex concepts such as well-being, textile comfort and marketing elementsand their integration in the design of new products. The related computational techniques includeclassical methods such as statistics, physical law based analytical equations, classical signal and imageprocessing and statistical pattern recognition, and intelligent techniques such as soft computing anddata mining. The selection of specific computational techniques is strongly related to the nature ofthe problem of interest. An optimal solution to a complex textile or garment problem can be found bycombining several complementary techniques in a suitable way.